Pregnant Women with Type 2 Diabetes Mellitus and Hypertension: A Physiological Overview - Muhsin Hmeadi Ubeid (Medical Journal of Babylon)
Background: Diabetes is one of the most common medical complications of pregnancy and it carries significant risk for the fetus and the mother. Objectives: This study includes hematological variables on type 2 diabetes mellitus (T2DM) in pregnant women that rely on insulin intake. Materials and Methods: In this study, there are 60 pregnant individuals with insulin-dependent T2DM and severe hypertension (HTN). In the governorate of Erbil, patients are seen in the medical labs of the Layla Qasim Center, Maternity Hospital, and Rizgary Teaching Hospitals. The control group consists of 20 healthy women. Results: The results demonstrate that pregnant women with diabetes, who are dependent on insulin intake, have a mean systolic blood pressure measurement of 153.8 ± 0.11 mm Hg, which is significantly higher than that of the control group. Blood levels of random glucose are significantly linked with HTN. Females with diabetes have a tiny bit fewer red blood cells (RBCs) than females without the disease. The hemoglobin (Hb) levels of pregnant patients with T2DM diabetes revealed lower levels compared to nondiabetic female group. Estimated sedimentation rate (ESR) levels are greater in T2DM than in the control group. The white blood cell (WBC) count is significantly higher in pregnant women with T2DM, particularly in the monocyte subtype of leukocyte, which exhibits a significantly elevated level. However, there is no difference observed in the proportion of high-type neutrophils in diabetes pregnant patients. The lymphocytes of pregnant T2DM patients who are dependent on insulin consumption do not demonstrate any relevance. Conclusion: Patients with hyperglycemia dramatically changed their total and differential leukocyte counts. This outcome was caused by an acute infection. Females with diabetes have fewer RBCs than those in the control group. High significance correlation exists between HTN and random blood glucose levels.